FAKTOR-FAKTOR YANG MEMPENGARUHI KOMPETENSI PENYULUH DALAM PEMBANGUNAN PERTANIAN DI PROVINSI JAWA BARAT* - Bambang G. Nuryanto; Sumardjo Sumardjo; Pang S Asngari; Djoko Susanto (Jurnal Penyuluhan Pertanian, 2020)
The objectives of this research were (1) to explore the competencies level of agricultureextension agents in agriculture development, and (2) to analyze the determinant factors whichinfluence the competencies of agriculture extension agents in agriculture development in WestJava Province. The respondents were specialist agriculture extension agents in four regenciesWest Java and amount 264. Collecting the data was done by distributed the structurequesioner with respondents. Data analysis was done by descriptive, correlation, regresion, andanova. The result of the research showed that (1) the competencies level of agricultureextension agents was low, and (2) the influence determinant factors for the competencies ofagriculture extension agents were trainning, self development and motivation of agricultureextension agents.